A128: Expression analysis 20 miRNAs in the clear cell renal cell carcinomas and surrounding tissues. Issue 1 (November 2015) - Pronina, I.; Loginov, V.; Kazubskaya, T.; Karpukhin, A.; Braga, E.
Abstract : RCC is one of the main problems in oncourology. MiRNA expression profiles are highly specific for malignant tumors of different locations, and can be used to detect pathological molecular biomarkers and to develop the optimal treatment for each patient. Selection of miRNAs associated with the formation and development of malignant tumors in the kidney was performed using computer databases miRWalk (http://www.ma.uni-hei-delberg.de/apps/zmf/mirwalk/ ) and miRBase (http://www.mir-base.org/ ). Paired samples of tumor and histologically normal tissue from 46 patients with RCC were studied. RNA was isolated by phenol–chloroform extraction and treated with RNase-free DNase after isolation. MiRNA expression analysis was performed by RT-qPCR using Applied Biosystems (USA) kits: TaqMan® MicroRNA Assays, TaqMan® MicroRNA Reverse Transcription Kit, TaqMan® Fast Universal PCR Master Mix (2x). RNU6B was used as reference miRNA. Quantity alterations of 20 microRNAs (hsa-miR-219, -203, -148a, -129, -9, -34a, -34b, -34c-3p, -127, -193a-5p, -191, -17, -24 -2 *, -339 -3p, -212, -375, -125b, -124a, -132, -137) were determined in samples of tumor compared to normal tissue biopsy from the kidney of each patient. It was shown that the expression of studied miRNAs usually decreased in RCC tumors. The largest decrease of expression was observed for miR-129, which expression was10–350-fold reduced in 93% of the samples ( P  < 0.05) with no change of expression in the remaining 7% of cases. MiR-375 (80% of cases, 10–270-fold decrease), miR-34b (79% of cases, 10–60-fold decrease), miR-124a (70% of cases, 10–200-fold decrease) also frequently showed reduced expression in tumors. In addition to the aforementioned ones, it had been shown that expression in the tumor compared with histologically normal tissue from the same patient was significantly decreased in more than half of the cases for miR-125b, miR-127, miR-203, miR-34c-3p, miR-9. Despite the fact that in 50% of cases decreased expression of miR-9 was detected, it was the only of studied microRNA with a significant increase in the expression in 21% of cases in 10–160 times ( P  < 0.05). Associations between the expression of investigated miRNAs and gender and age were not noted. Dealing with each miRNA alone, we could not detect the dependence of expression alteration of 20 selected miRNAs from the stage or degree of tumor differentiation of the studied RCC samples. However, the analysis of the expression profile of 20 miRNAs in complex showed that decreased expression was observed much less frequently in the samples with a later RCC stage than in samples with early RCC stage. For example, in a tumor sample of a patient with stage IV (T3aN2M1) expression was reduced only for miR-129 and miR-375 in 10 times for each miRNA, while the expression of miR-9 was increased. In samples with stage III expression was reduced in 2 or 4 out of the selected 20 miRNAs, in samples with stage I expression decrease was observed for 9 out of 20 studied miRNAs. Since kidney tissue from the same patient was taken as the control, it could be assumed that the absence of expression decrease in studied 20 miRNAs in tumors was due to a decrease in their expression in the surrounding tissues, which eliminated the difference in the quantity of miRNAs in tumors and surrounding tissues. An additional experiment, in which kidney tissue from healthy donors with no history of cancer was taken as a control, showed decreased expression of miR-125b, miR-124a, miR-127, miR-203, miR-34c- 3p, miR-9, miR-129, miR- 34b in histologically normal tissue of patients with RCC. There was identified a group of miRNAs out of studied 20 ones which may be involved in the progression of RCC, they were at least miR-129, miR-375 and miR-9. Expression characteristics of miRNAs require further study and may be used as biomarkers.